Penerapan Multi Criteria Decision Untuk Rekomendasi Program Ekstrakulikuler Di Sekolah Menengah Atas - Adela Hutauruk, Tascha (Buletin Ilmiah Informatika Teknologi, 2025)
The rapid development of computer technology has had a significant impact on various sectors, including education. The utilization of information technology systems plays a crucial role in supporting data processing and effective, efficient decision-making processes. At SMA Swasta Panti Budaya, the selection of extracurricular activities by students is still conducted manually, which often leads to confusion in choosing activities that match their interests and potential. This can result in a lack of student participation in extracurricular programs and the failure to develop their talents and interests. Therefore, a decision support system is needed to accurately recommend extracurricular activities based on each student's potential. This study aims to design and develop a recommendation system using the Multi-Criteria Decision Making (MCDM) approach, specifically the Elimination and Choice Translation Reality (ELECTRE) method. This method is capable of selecting the best alternative from several options based on specific criteria. With the implementation of this system, the school is expected to provide more accurate and appropriate recommendations for extracurricular activities, thereby supporting students in achieving their full potential and academic success.